Mengurai Benang Kusut Indikasi Kematian Massal Eksistensi Tuhan di Abad Globalisasi - Nurul Anam (Ulumuna, 2009)
The “post god” era represents a period indicating about mass death of god and describing a human life that existentially "kill" god position, and not be trapped at formally absolute dogmatic. In this era, new-Nietzsche god faces with very high desire of absolute power emerge. They disobey there is something else takes a grip on them. They are conscious that there is God, but that is only at formal testimony level, not at substantial-operational level. If this phenomenon is analyzed farther, then it will be clear that the emergence of new-Nietzsche god faces in the “post god” era has caused a crisis of god consciousness. Thereby, deconstruction of god consciousness to change new-Nietzsche god to become perfect humanity and transform him to become God proxy in the world is a kind of progressive and meaningful action to the better future of world civilization.